Neonatal outcomes of eclamptic mothers in a tertiary government rural teaching hospital of Eastern India - Bandyopadhyay, Santanu; Das, Rajib; Burman, Medhatithi; Datta, Asok Kumar (Indian Journal of Child Health, 2019)
Background: Studies related to the neonatal outcomes of eclamptic mothers in a rural sociodemographic setting of India are not abundant. Objective: The objective of the study was to identify and assess the significance of the neonatal outcomes of eclamptic mothers in a rural population. Materials and Methods: This was a prospective, cross-sectional, observational, and epidemiological study in a tertiary care government teaching hospital catering rural agro-based population of Eastern India. The study was conducted during April 2012–March 2013 and consisted of two groups. One group comprised neonates born to 100 consecutive eclamptic mothers and another consisted of neonates of 100 non-eclamptic (control) mothers. Both groups were statistically matched after selection through inclusion-exclusion criteria. Results: The majority of eclamptic mothers were unbooked, primigravidae (86%), in late teens (66%), belonging to socioeconomic Class IV (92%) of modified Kuppuswamy scale (2007). About 72% of neonates were born with one or more adverse neonatal outcomes (p<0.001). Neonatal outcomes as observed in this study were prematurity (40%, p=0.001), low birth weight (LBW) (60%, p<0.001), intrauterine growth retardation (IUGR) (12%, p=0.032), and birth asphyxia (33%, p=0.016), while hypoxic-ischemic encephalopathy, early-onset sepsis, early neonatal death, and stillbirth were not found to be statistically significant. Late preterm births were also significant (p=0.004). Conclusion: Eclampsia in the rural population is an important cause of significant neonatal morbidity in terms of prematurity, LBW, IUGR, and birth asphyxia. It is a significant risk factor for late preterm births as well.